Organizational Capacity of the PMPTSP Office of Bandar Lampung City in Implementing A Collaborative and Dynamic Work System - Iswardi, Benny; Deddy Supriady Bratakusumah (International Journal of Social Science and Business, 2024)
Organizational change capacity determines how easily an organization can implement organizational change. This study aims to provide an overview of the organizational capacity analysis of the Bandar Lampung City PMPTSP Office in implementing a new collaborative and dynamic work system. This research is qualitative with a descriptive approach. The results of this study show that the organizational capacity of the Bandar Lampung City PMPTSP Office can support the implementation of a new collaborative and dynamic work system, especially in the leadership aspect. Strong leadership commitment with transformational and transactional leadership styles is a modality for the organizational capacity of the PMPTSP Office to overcome all challenges and obstacles in the early stages of the process and the sustainability of organizational change. The Head of PMPTSP Bandar Lampung City Office has actualized the transformational and transactional leadership style optimally. This is evidenced by various assessment achievements with good predicates and awards that have been received from various parties. The organizational capacity of the PMPTSP Office to make changes is getting stronger with the commitment and support of the Mayor of Bandar Lampung to improve public services. Budget constraints, especially for human resource development, can be overcome by developing knowledge sharing through internal meetings and discussions and creating social media (WhatsApp and Telegram). The implication of this research is the importance of strengthening leadership commitment and support from related parties in facing challenges and obstacles in organizational change.